Rupture of gravid rudimentary horn - Anand, Diti; Dukare, Shital Shivajirao; Yelikar, Kananbala Avinash; Bhingare, Prashant E.; Gadappa, Shrinivas N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Pregnancy in rudimentary horn is a rare occurrence with incidence of less than 1 in 150,000. Pregnant rudimentary horn can present with wide range of symptoms that may be similar to ectopic pregnancy or may remain silent with features of normal pregnancy. Management is typically resection of the rudimentary horn by either laparotomy or laparoscopy. This case has been reported for its rarity and dilemma in diagnosis which is a case of a 21 years old, married since 1 year primigravida nullipara presented with 3 and half month amenorrhea with acute abdomen since 2 days. Her vitals were stable with severe anaemia (Hb 5 gm%). Her obstetric USG showed features of 14 weeks foetus in probably rudimentary horn on left side. Right sided horn showed normal endometrial thickness. Patient’s emergency laparotomy was done with excision of rudimentary horn containing the pregnancy. The wall of rudimentary horn showed rupture with hemoperitoneum 200 ml. To conclude, uterine abnormalities are rarely encountered in pregnancy. Attempts should be made for early diagnosis to avoid maternal mortality. Ultrasound in the first trimester may provide a means of an early diagnosis. It requires proper history, high level of suspicion, routine early pregnancy scan and documentation of operative findings. Rudimentary horn pregnancy should always be kept as differential diagnosis in early second trimester pregnancy with acute abdomen.